Telemodernities : television and transforming lives in Asia - Lewis, Tania; Martin, Fran, 1971-; Sun, Wanning, 1963- (Console-ing passions., 2016)
Tania Lewis, Fran Martin, and Wanning Sun analyze the complex social and cultural significance of lifestyle television programming in China, India, Taiwan, and Singapore, showing how it adds insight into late Asian modernity, media cultures, and broad shifts in the nature of private life, identity, citizenship, and social engagement.